Acute myocardial infarction and left ventricular thrombus in a young male with thromboangiitis obliterans: a case report and literature review - Junyan Zhang; Kai Li; Li Rao; Yong He; Zhongxiu Chen; Xin Wei (Journal of Cardiothoracic Surgery)
Abstract Thromboangiitis obliterans (TAO) is an inflammatory vascular disease that primarily affects the small- and medium-sized arteries of the extremities. Coronary artery involvement in TAO is rarely reported, and we present the first case of TAO involving the coronary arteries with concomitant left ventricular thrombus. In addition, our case report includes a literature review on coronary artery involvement in TAO and draws comparisons with systemic vasculitis with coronary artery involvement. The case report and literature review aims to offer physicians valuable insights for diagnosis and treatment of TAO with coronary arteries involvement, while also advocating for increased research efforts to explore therapeutic strategies for this rare condition, including both pharmacological treatment and interventional therapy.